Difference between the rotational throw and the glide throw techniques in shot put event - Aoyama, S.; Fukuda, S.; Aoyama, T.; Tsunoda, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In recently, many shot put throwers performing the rotational throw technique is increasing in shot put event. What are some of the advantage and disadvantage of the rotational throw and the glide throw techniques. The purpose of this study was to clarify the difference of technical factors between the rotational throw and the glide throw techniques for design of skill training program. Methods: Subjects were seven male Japanese right-handed elite shot put throwers who can use the rotational throw and the glide throw techniques (age:22.7±2.3yrs, height:176.6±6.8cm, body weight:107.6±15.1kg, rotational throw:14.1±1.3m, glide throw:13.4±1.5m). All the subjects performed total six throws that three rotational throw technique and three glide throw technique same as a competition rules. Rotational throw technique and glide throw technique were measured by 3-D analysis (APAS) that was analyzed for release speed, release angle, release high, shot acceleration (horizontal, vertical and total acceleration) and shot movement speed. Throwing movement was divided by turn-phase and push-phase during shot put movement. Results: Shot put performance was significantly related to the release speed in both throw techniques (rotational throw: r=0.501, glide throw: r=0.579). Shot acceleration of vertically and total acceleration in rotational throw technique were significantly higher than glide throw technique during the push-phase. Similarly, shot moved speed in the rotational throw technique was significantly higher than the glide throw technique during the on turn-phase. Discussion: From these results, it was cleared that developing of the release speed is most important factor in shot put for both throwing techniques. The rotational throw technique to the pushing vertical direction may important factor during the push-phase. And also, the rotational throw technique may energy stored on lower limb and trunk during the turn-phase in the rotational throw skill training.